The Establishment And Activity Of Private Schools In Uzbekistan - Ulugbek Yuldashev (Periodica Journal, 2026)
One of the key reforms aimed at modernizing the education system in Uzbekistan has been the development and institutionalization of the non-state education sector. In the context of large-scale educational transformations carried out within the framework of the “New Uzbekistan” development strategy, private schools have emerged as an important component in ensuring diversity, competitiveness, and quality in general secondary education. This article examines the main socio-economic, demographic, and institutional factors that contributed to the emergence of non-state general secondary schools in Uzbekistan. Particular attention is paid to the goals and functions of private schools, including their role in meeting growing educational demand, introducing innovative teaching methods, and integrating international educational standards.
Keywords: New Uzbekistan; non-state education; private schools